EVALUASI KESIAPAN DAN KEPUASAN PENGGUNA PADA IMPLEMENTASI e-PROCUREMENT (Studi Kasus: Bagian Pengadaan Barang dan Jasa PT. PLN (Persero) Distribusi Jateng & DIY) - Bambang Tetuko; Darminto Pujotomo; Susatyo Nugroho W (Industrial Engineering Online Journal, 2012)
ABSTRAK Dalam implementasi e-Procurement PT. PLN (Persero) Distribusi Jateng & DIY masih terdapat berbagai permasalahan dan kendala yang dihadapi baik dari segi kesiapan penyedia layanan e-Procurement, kesiapan pengguna e-Procurement dan dari segi kepuasan pengguna e-Procurement. Oleh sebab itu perlu dilakukan evaluasi tingkat kesiapan dan kepuasaan pengguna pada proses implementasi e-Procurement untuk memberikan rekomendasi serta langkah perbaikan. Penelitian ini menggunakan model e-Learning Readiness dan End-User Computing Satisfaction (EUCS). Dari hasil pengolahan statistik deskriptif diperoleh bahwa tingkat kesiapan untuk variabel people resourcess, people skill, technology resourcess dan attitude of innovation dapat dikatakan not ready needs some work, sedangkan untuk variabel resourcess of self development, skill of self development, attitude of self development, technology skill dan attitude technology dapat dikatakan ready but needs a few improvement. Sedangkan tingkat kepuasan untuk variabel accuracy, format, ease of use dan timeliness pengguna menyatakan puas, sedangkan untuk variabel content pengguna menyatakan netral.  ABSTRACT In implementation e-Procurement PT. PLN (Persero) Distribution Jateng & DIY still many problems and obstacles encountered readiness of service provider e-Procurement, readiness of users and user satisfaction of e-Procurement. Therefore it is necessary to evaluate readiness level and user satisfaction in process implementing e-Procurement to provide recommendations and determine improvement measures. This study uses model e-Learning Readiness and End-User Computing Satisfaction (EUCS). From the results of descriptive statistical processing that readiness level for the variable resourcess people, people skills, technology and attitude of innovation resourcess can be said not ready needs some work, while for the variable resourcess of self development, skill development of self, attitude of self development, technology skills and technology attitude can be said ready but needs a few improvement. While the level satisfaction for the variable accuracy, format, ease of use and timeliness users said they were satisfied, while for the variable content users said they were neutral.